Seeding equatorial spread F with turbulent gravity waves: Phasing effects. Issue 1 (8th January 2015) - Wu, T.‐W.; Huba, J. D.; Krall, J.; Fritts, D. C.; Laughman, B.
Abstract The Naval Research Laboratory (NRL) SAMI3/equatorial spread F (ESF) three‐dimensional ionosphere model is used to study the initiation and development of the large‐scale plasma bubbles in the postsunset equatorial F region by turbulent gravity waves. The gravity wave turbulence is obtained from a three‐dimensional anelastic, finite‐volume model. We show that the phasing of gravity waves at conjugate regions in the ionosphere can enhance (in phase) or reduce (out of phase) the effective seed of the instability. The nonlocalized nature of the effective seed may contribute to the observed day‐to‐day variability of ESF. Additionally, we find that the zonal and vertical wind perturbations associated with the gravity waves are most effective in seeding ESF bubbles; perturbations of the meridional wind are relatively ineffective.